Capital Asset Pricing Model (CAPM) Analysis as a Basis Decision Making to Invest in Shares in Financial Sector Companies - Hasmalini, Nini; Heikal, Jerry (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
This research was conducted to analyze the feasibility level of investment in BEI index shares for the 2023 period using the Capital Asset Pricing Model (CAPM) method in determining investment decisions. The type of quantitative research is descriptive. The population of this research is financial sector companies, Distribution which are listed on the index IDX Industrial Classification or IDX-IC for the period November 2022 – October 2023 . The sample used was 10 shares of financial holdings industry companies determined by the researcher. This research uses Microsoft Excel linear regression data analysis to determine the beta coefficient of the Capital Asset Pricing Modeling (CAPM) method and compares the expected return with the stock market rate of return during the observation period to better differentiate between efficient and inefficient stocks. The observation results show that 8 companies have efficient shares and 2 companies have inefficient shares which can be seen on the SML Security Market Line (SML) graph or CAPM model securities market line (GPS) for efficient shares and inefficient shares.